Social Capital and Factors Related to Stroke Risk in Ponorogo Hospital: Structural Equation Model Application - Rohmah, Lailatul; Rahardjo, Setyo Sri; Murti, Bhisma (Journal of Epidemiology and Public Health, 2020)
Background: Stroke is a non-communicable disease that ranks the second leading cause of death in the world. As many as 17 million pa